Evaluation of chemokine CXCL10 in human gingival crevicular fluid, saliva, and serum as periodontitis biomarker - Aldahlawi S; Youssef AR; Shahabuddin S (Dove Medical Press, 2018)
Salwa Aldahlawi,1 Abdel-Rahman Youssef,1 Syed Shahabuddin2,3 1Department of Basic and Clinical Oral Sciences, College of Dentistry, Umm Al-Qura University, Makkah, Saudi Arabia; 2Abbvie, North Chicago, IL,USA; 3Deportment of Biology, City Colleges of Chicago, Chicago, IL, USA Purpose: The aim of this study was to evaluate CXCL10 as a biomarker for periodontitis by determining the CXCL10 levels in saliva, serum, and gingival crevicular fluid (GCF) samples from periodontally healthy control subjects and adult subjects with chronic periodontitis.Patients and methods: Adult patients seeking dental treatment at Umm Al-Qura University dental clinic underwent a complete periodontal examination, and saliva, serum, and GCF samples were collected. Subjects were classified as chronic periodontitis patients (n=31) if they have a periodontal probing depth (PD) of ≥4 mm and/or clinical attachment level (CAL) of ≥3 mm in >30% of the teeth. The control group (n=25) had PD ≤3 mm and/or CAL ≤2 mm. ELISA was performed to determine the concentration of CXCL10 in saliva, serum, and GCF samples. Student’s t-test was carried out to evaluate the significant difference between different groups. Spearman’s correlation test was used to analyze the relationship between the levels of CXCL10 and the clinical periodontal parameters. P-value of ≤0.05 was considered significant.Results: Significantly higher concentrations of CXCL10 were found in saliva and serum in chronic periodontitis patients as compared with the controls (272±60.4 pg/mL and 72±13.4 pg/mL vs 130±22.2 pg/mL and 44.08±4.5 pg/mL, P≤0.05). The CXCL10 levels in GCF were higher in the periodontitis group as compared with the control group (66.36±32.0 pg/mL and 44.56±17.5 pg/mL, respectively); the difference did not reach statistical significance (P≥0.05). Moreover, serum CXCL10 level was significantly higher in periodontitis patients with moderate to severe bone loss as compared with those with mild bone loss (71.05±4.7 pg/mL vs 54.8±7.7 pg/mL, P≤0.05). The serum CXCL10 levels were found to be related to CAL measurements (r=0.3, P=0.026), while the saliva CXCL10 levels were related to PD measurements (r=0.8, P=0.0007).Conclusion: CXCL10 is significantly increased in periodontitis subjects as compared with controls and could be used as a marker for periodontal disease. Keywords: periodontal disease, alveolar bone loss, gingival crevicular fluid, saliva, serum, biomarker, CXCL10, IP-10